2006
DOI: 10.1086/508495
|View full text |Cite
|
Sign up to set email alerts
|

Functional Comparison of T Cells Recognizing Cytomegalovirus pp65 and Intermediate‐Early Antigen Polypeptides in Hematopoietic Stem‐Cell Transplant and Solid Organ Transplant Recipients

Abstract: The functional status of cytotoxic T lymphocyte (CTL) populations recognizing cytomegalovirus intermediate-early antigen (IE1) and pp65 polypeptides was investigated in peripheral blood mononuclear cells from hematopoietic stem-cell transplant (HSCT) and solid organ transplant recipients. Combined flow-based CD107a/b degranulation/mobilization and intracellular cytokine (ICC) assays using peptide libraries as antigens indicated that a significantly higher proportion of pp65-specific CTLs were in a more mature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 48 publications
(74 reference statements)
4
44
0
Order By: Relevance
“…Using a combination of the CD107 mobilization assay and intracellular cytokine staining, there have been limited reports of heterogeneity in the degranulating and cytokine producing properties of human CD8+ T lymphocytes responding to epitopes in HIV, CMV, and dengue virus Lacey et al, 2005;Lacey et al, 2006;Mongkolsapaya et al, 2006). Similar to our observation in rhCMV-specific CD8+ T lymphocytes, human CMV-specific CD8+ T lymphocytes targeting different epitopes showed variation in their degranulating and cytokine producing capacity (Lacey et al, 2005;Lacey et al, 2006).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Using a combination of the CD107 mobilization assay and intracellular cytokine staining, there have been limited reports of heterogeneity in the degranulating and cytokine producing properties of human CD8+ T lymphocytes responding to epitopes in HIV, CMV, and dengue virus Lacey et al, 2005;Lacey et al, 2006;Mongkolsapaya et al, 2006). Similar to our observation in rhCMV-specific CD8+ T lymphocytes, human CMV-specific CD8+ T lymphocytes targeting different epitopes showed variation in their degranulating and cytokine producing capacity (Lacey et al, 2005;Lacey et al, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…This property has recently been exploited for flow-cytometric identification of CTL at the single-cell level. Simultaneous characterization of cytolytic and cytokine-secreting effector functions at the single-cell level have shed light on the functional heterogeneity of virus-specific CD8+ CTL in mice and humans Wolint et al, 2004;Lacey et al, 2005;Betts et al, 2006;Lacey et al, 2006;Mongkolsapaya et al, 2006). In this study, we have optimized the flow-cytometric technique for detection of degranulating CD8+ T lymphocytes in rhesus macaques, and used it to characterize the functional properties of rhesus cytomegalovirus (rhCMV)-specific CD8+ T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Using the panel of tetramers we observed a decreased frequency to IE-1 at less than 100 days in comparison to pp65 and pp50. Interestingly Lacey et al 37 have also observed comparable functional responses to pp50 and pp65 post-SCT, but impaired responses to IE-1. The CD8 þ immune response to IE-1 peptides was not predictive of increased protection from viral reactivation in our study supporting two other HSCT studies 38,39 but in contrast to other studies in solid organ transplantation.…”
Section: Discussionmentioning
confidence: 88%
“…These included the IE-1, and the immune response against this protein has been shown to be an important determinant for control of CMV reactivation following solid organ transplantation. 36 Functional differences between pp65 and IE-1-specific CD8 þ T cells have been reported in the SCT setting which may influence their relative efficacy in control of viral reactivation, 37 however T-cell function could not be addressed here. We also studied the CD8 þ immune response to a peptide from pp50 from which a number of potent immunodominant peptides have now been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Although pp65 by itself is a prominent target of the CD4 and CD8 T cell responses following natural infection [23][24][25], other proteins like the non-structural, regulatory IE1-protein (ppUL123) are also targeted by the immune system [26,27]. Consequently, inclusion of such antigens in a vaccine formulation may be important to induce a broad immune response [15,[26][27][28][29][30]. We have started a project to broaden the antigenic content of DB.…”
Section: Introductionmentioning
confidence: 99%